2010
DOI: 10.1016/j.molcel.2010.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of TIP60 by Human Papillomavirus E6 Results in Attenuation of TIP60-Dependent Transcriptional Regulation and Apoptotic Pathway

Abstract: The TIP60 tumor suppressor is a histone acetyltransferase involved in transcriptional regulation, checkpoint activation, and p53-directed pro-apoptotic pathways. We report that Human Papilloma Virus (HPV) E6 destabilizes TIP60 both in vivo and in vitro. TIP60 binds to the HPV major early promoter and acetylates histone H4 to recruit Brd4, a cellular repressor of HPV E6 expression. Both low- and high-risk HPV E6 destabilize TIP60, thereby derepressing their own promoter. Destabilization of TIP60 by HPV E6 also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
144
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(153 citation statements)
references
References 61 publications
7
144
0
Order By: Relevance
“…K120 acetylation is crucial for p53-mediated apoptosis but has no obvious effect on p21 expression, an essential target of p53-mediated growth arrest. Notably, although Tip60 is required for K120 acetylation of p53 in vivo, the levels of K120 acetylation are dynamically regulated in vivo and the interaction between p53 and Tip60 is not very stable, indicating that additional regulators may play a role in controlling K120 acetylation and subsequent p53-mediated apoptotic response (18)(19)(20). Through biochemical purification, we identified p90 as a unique regulator for p53.…”
mentioning
confidence: 97%
“…K120 acetylation is crucial for p53-mediated apoptosis but has no obvious effect on p21 expression, an essential target of p53-mediated growth arrest. Notably, although Tip60 is required for K120 acetylation of p53 in vivo, the levels of K120 acetylation are dynamically regulated in vivo and the interaction between p53 and Tip60 is not very stable, indicating that additional regulators may play a role in controlling K120 acetylation and subsequent p53-mediated apoptotic response (18)(19)(20). Through biochemical purification, we identified p90 as a unique regulator for p53.…”
mentioning
confidence: 97%
“…At this juncture, our search for other probable acetyl transferases revealed an increment in the endogenous tumor suppressor acetyl transferase Tip60 protein expression in the HPV18-infected cervical carcinoma cells under curcumin-treated conditions. It has been reported that whereas Tip60 promotes the proapoptotic Lys-120 acetylation of p53, thereby executing its anti-tumor function (14), it is degraded by the proto-oncogene E6 in the cervical adenocarcinoma cells (15). In our experimental sets, curcumin-induced repression of E6 via SMAR1 rescues Tip60 from E6-mediated degradation and promotes acetylation and activation of p53 to initiate downstream apoptotic pathways.…”
Section: Discussionmentioning
confidence: 59%
“…(38, 39). However, Tip60 has been shown to be down-regulated in HPV18-infected cervical adenocarcinoma cells in which HPV 18 E6 degrades it in a proteosome-dependent pathway (15). Our results depicted a significant restoration and increase in Tip60 expression in HeLa cells after curcumin treatment in a time-dependent manner (Fig.…”
Section: Inhibition Of E6 Reinstalls Apoptotic Program In Hpv18-infecmentioning
confidence: 50%
See 2 more Smart Citations